Endoscopic Ultrasound–Guided Gastrojejunostomy for Malignant Gastric Outlet Obstruction in a Patient With a Previous Liver Transplant and Pancreaticoduodenectomy. Issue 1 (19th January 2022) - On, Wei; Huggett, Matthew T.; Upasani, Vivek; Paranandi, Bharat
ABSTRACT: A 29-year-old man underwent a liver transplant 5 years earlier for primary sclerosing cholangitis and a subsequent completion pancreaticoduodenectomy after the discovery of a cholangiocarcinoma on histological analysis of his explant. He presented with gastric outlet obstruction secondary to recurrent peritoneal malignant disease–causing extrinsic compression at the gastroenterostomy site. After multidisciplinary team discussions, an endoscopic ultrasound–guided gastrojejunostomy was performed, resulting in technical and clinical success. We report the first application of endoscopic ultrasound–guided gastrojejunostomy in a patient with the aforementioned postsurgical anatomy.